INFLUENCE OF SEED PRIMING ON DROUGHT INDICES OF MAIZE - DR. SURESHBABU (Global Journal of Plant and Soil Sciences, 2022)
Objective of this investigation is to study the influence of seed priming treatments on drought indices in maize (Zea mays L.). The experiment was carried out during kharif 2016 -17 at research farm JNKVV, Jabalpur (MP) which was laid out in a randomized block design replicated thrice. The treatments comprised of nine seed priming treatments in maize cv, African tall viz., water, ZnSO4 @ 0.5%, KNO3 @ 0.5% & amp; KH2PO4 @ 0.5% for 6 and 12 hrs and control which were assessed for drought indices. The seed priming treatments showed variable response for most of the traits. Water primed for 12 hrs indicated the highest values for drought indices. Water primed for 12 hours had highest desiccation tolerance (619.93) and leaf water potential (-4.83). KNO3 primed for 12 hours (11.69) possessed higher water use efficiency which suggested that this treatment may be induced in the maize genotypes which are cultivated in drought sensitive areas. KH2PO4 primed for 12 hours (81.39) was associated with the highest relative water content followed by water primed for 6 and 12 hours and had lowest (18.61) water saturation deficit. This is a desirable character which a treatment should possess for drought affected areas.